Comparative study of Fine-Needle Aspiration Cytology and Histopathological diagnosis of salivary gland swelling - J, BALAPRASANTH; P B, Vinod (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Fine-needle aspiration cytology (FNAC) of salivary gland swelling helps differentiate benign and malignant lesions, thereby allowing clinicians to plan proper management. Ultrasound-guided FNAC is more accurate than other methods of FNAC. It is simple and safe and lacks significant complications. It is also inexpensive and can be repeated if needed. Methods: This study is a prospective study of 80 patients subjected to FNAC followed by surgery and histopathological examination, from September 2017 to July 2019. Histopathology reports were compared with the preoperative FNAC reports. In all 80 cases, informed consent was obtained prior to surgery. Results: True-positive, true-negative, false-positive, and false-negative rates for carcinomatous lesions of salivary gland swelling were assessed. Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 81.82%, 97.10%, 81.82%, 97.10%, and 95%, respectively for FNAC when compared against histopathology. Conclusion: FNAC is a sensitive, specific, and accurate diagnostic test used for the preoperative evaluation of patients with salivary gland swelling. FNAC is very commonly used as an initial routine investigation.